Facilitating effect of the hypnotically altered state of consciousness on decision-making in a situation modeling real-life - Z. A. Kovács; S. László; A. Albert; Z. Janka; I. Szendi (European Psychiatry, 2024)
Introduction Numerous studies have shown a link between hypnotic susceptibility, the hypnotically altered state of consciousness, and the intensity of experienced emotions (De Pascalis et al., 1987; De Pascalis, Marucci, & Penna, 1989; Bryant & McConkey, 1989; Crowson, Conroy, & Chester, 1991; Crawford, Kapelis, & Harrison, 1995). One of the most suitable experimental psychological methods for modeling real-life decisional conditions is the Iowa Gambling Task (IGT) (Bechara, Tranel, & Damasio, 2000). Hypnosis has the potential to provide several benefits in decision-making, although there is limited scientific research on the subject.